Identification of a mycorrhiza isolate from Paphiopedilum barbatum (Lindl.) pfitzer from Ex situ location and determination of its growth-enhancing capabilities - Idris, Nurul Aliaa (2010)
Orchids and mycorrhiza are known to have a symbiotic relationship that function particularly in seed germination and also in promoting overall plant growth. It is believed that a certain orchid mycorrhiza that functions to enhance plant growth also lives symbiotically in the roots of Paphiopedilum barbatum. Thus, the objectives of this research are to identify the mycorrhizal fungi that form a symbiosis with the terrestrial tropical orchid, P. barbatum and evaluate its capabilities to enhance growth in certain in vitro Paphiopedilum seedlings. Mycorrhizal fungi were isolated from the roots of P. barbatum collected from five different locations in Peninsular Malaysia. Isolation of fungi was carried out according to the Currah method for initial morphological identification and then through molecular identification using the internal transcribed spacer (ITS) region of nuclear ribosomal DNA of the isolates. The identified mycorrhiza was then inoculated on in vitro selected Paphiopedilum seedlings on a double slanting media to observe mycorrhization and the occurrence of enhancement of plant growth. Only one mycorrhiza was isolated and identified; namely Tulasnella calospora (anamorph: Rhizoctonia repens) which is a ubiquitous orchid mycorrhiza. Phylogenetic analyses with sequences originating from different hosts from different countries indicated a close genetic relatedness of the sequences studied. In vitro inoculation of T. calospora on seedlings from the Paphiopedilum genus after incubation for 24 weeks showed a significant 1.1% increase in fresh weight in P. rothschildianum with 68% root mycorrhization. However, no significant growth was observed in the seedlings of P. sanderianum, P. gigantifolium x P. rothschildianum and P. esquirolei x P. rothschildianum when inoculated with T. calospora after incubation for 24 weeks even though each had 32%, 24% and 13% root mycorrhization. This preliminary finding present an insight into the orchid mycorrhiza of the Paphiopedilum but a more extensive study is needed to further explore this symbiotic relationship and furthermore contribute in developing a beneficial application whether commercially or for the conservation of this genus.